2001
DOI: 10.2118/72050-pa
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene Stability in Crude Oils

Abstract: The influence of different factors on the asphaltene stability in crude oils was evaluated. Compositional studies and structural characterization of resins and asphaltenes were carried out to study a possible relationship between these properties and asphaltene deposition behavior. Asphaltenes were obtained by precipitation with n-heptane and characterized by elemental analysis and spectroscopic techniques. Low hydrogen to carbon ratios, high aromaticities, and high condensation of aromatic rings were the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 17 publications
1
27
0
Order By: Relevance
“…Furthermore, that asphaltenes F40/60 appeared to have the largest average size and also the highest aromaticity suggests that this subfraction contained the molecules with the highest molecular weight. Such results would also be in agreement with studies by other researchers who have proposed that there is a relation between high aromaticity and high molecular weights of asphaltenes and stability problems with crude oils [18,19].…”
Section: Correlation Of Average Diffusion Coefficients To Sizesupporting
confidence: 93%
See 1 more Smart Citation
“…Furthermore, that asphaltenes F40/60 appeared to have the largest average size and also the highest aromaticity suggests that this subfraction contained the molecules with the highest molecular weight. Such results would also be in agreement with studies by other researchers who have proposed that there is a relation between high aromaticity and high molecular weights of asphaltenes and stability problems with crude oils [18,19].…”
Section: Correlation Of Average Diffusion Coefficients To Sizesupporting
confidence: 93%
“…Furthermore, current research suggests that certain characteristics of asphaltenes, e.g., low aromaticity and low molecular weight, are essential for the stability of crude oils [17][18][19][20], and that these factors may be even more important than the actual asphaltene content of an oil. Hence, one question that invariably occurs is whether the stability and solubility of asphaltenes can be correlated to their size and molecular weight [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…This is an important information as it has been suggested that there is a direct relationship between high aromaticity and high molecular weight asphaltene molecules and stability issues with crude oils. 88,89 It has been concluded by Ostlund et al 84 that the structural variations between the subproportions of Cold Lake asphaltenes may alter the aggregate-establishing characteristics of the asphaltene molecules, although the asphaltene samples do not differ significantly in terms of heteroatom content as revealed by an elemental analysis.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…30 For instance, the unstable character of crude oil samples was related to low hydrogen-to-carbon ratios and high aromaticity of asphaltenes. 31,32 Accordingly, further research efforts are necessary to include the properties of asphaltenes within indexes or methodologies to count on reliable and universal tools to predict the stability of crude oils.…”
Section: Resultsmentioning
confidence: 99%